Microdosimetry test on double layer beam shaping assembly neutron beam as a boron neutron capture therapy neutron source using PHITS code - Bilalodin; A. Haryadi; Sehah; Zusfahair; Y. Sardjono; R. Tursinah (Âderna Fìzika ta Energetika)
A microdosimetry test on a double layer beam shaping assembly (DLBSA) neutron beam has been carried out using the particle and heavy ion transport code system (PHITS). The test aims to understand the mechanism of interactions between neutrons and microcells and to determine the linear energy transfer (LET) and the relative biological effectiveness (RBE) values of the DLBSA neutron beam. The test was carried out by interacting a neutron beam with microcells containing 10B using a boron concentration of 70 ppm. The neutron source used comes from a 30 MeV cyclotron-based DLBSA. The simulation results show that the interaction of neutrons with microcells occurs through scattering, reflection, and absorption reaction mechanisms. The results of the microdosimetry test showed that the peak LET value of α-particles was 100 keV/μm and 7Li was 200 keV/μm, with an RBE value for α of 9.83 and 7Li of 6.11.